Kinematical Motor Analysis Of Kurdistan Gymnasts’ Handstand On The Mat In Floor Exercises - Abbas, Saadullah (Journal of Physical Education, 2016)
Gymnastics is considered on of the most difficult events due to its motor performance difficulty. The researchers noticed the difficulties faced by gymnasts that lead them to lose their skill and artistic performance. The researchers analyzed handstand and specified the most important values of this skill. The aim of the research is to identify the kinematical values of handstand of Kurdistan gymnast on the mat during floor exercises, in addition to that, the research aimed at identifying the differences among these values. The subjects were Kurdish gymnasts in college of physical education gymnasium in Salah anl deen/ Arbil. The research was conducted from 17/4/2014 – 25/6/2014. The data was collected and treated using proper statistical methods.The researchers concluded that hip joint value is larger than 180 in all gymnastics especially at the final phase due to weakness in balance and stability. Finally the researchers recommend that all Kurdistan club coaches should do artistic evaluation of motor analysis to clarify the development of artistic performance of different gymnastic movements. Finally the researchers recommended paying attention to mechanical and analytical bases of artistic performance for all gymnastic movements to identify peak performance and early detection of weakness in players